Valorizing staple Native American food plants as a food resilience resource - Winstead, Daniel J.; Jacobson, Michael G.; Di Gioia, Francesco (Frontiers in Sustainable Food Systems, 2023)
Introduction Increased risks from global climate change and sun-blocking global catastrophic risks (such as a nuclear winter), warrant the reevaluation of our food systems and their resilience to these climatic changes. Increasing native agrobiodiversity is a simple way of increasing food system resilience, and despite the vast amount of native genetic resources available in North America, the United States has shown little systematic effort to improve its agrobiodiversity. Methods We use a systematic literature review of staple Native American food plants (NAFPs) to determine the current state of research interest among them and suggest species of interest for domestication. The nutrient profiles and nutrient adequacy scores for the most researched staple NAFPs were also collected and calculated. Results A total of 174 Staple NAFPs were evaluated through systematic review, resulting in a total of 5302 peer-reviewed articles searched. Our findings show that most NAFPs are understudied and are more commonly seen by the agricultural community as weeds. However, there are a few that have current scientific interest in their value as a potential crop. Discussion We discuss the 24 most researched NAFPs and their nutritional content. We also discuss potential actions, protocols, and ethical issues regarding future steps in using NAFPs to increase agrobiodiversity and food resilience in the United States through more resilient agroforestry systems.